The use of Polish Sign Language (PJM) in bilingual textbooks for deaf students in Polish schools. Issue 3 (3rd May 2020) - Rutkowski, Paweł; Mostowski, Piotr
ABSTRACT: This article describes the project of producing Polish Sign Language (PJM) translations of a series of Polish primary-school textbooks. We discuss the multimedia software application that presents the resulting bilingual textbooks, which allows video clips to be played back by clicking on the corresponding original Polish text. We also explain the methodological choices and principles that guided the project and examine the anticipated impact of the project for deaf students in Polish schools, for their teachers, and for the PJM speaking community at large.